Study of the Effect of Various Methods for Removing Sealant Residues from the Pulp Chamber on Microleakage (Laboratory Study) - برازي محمد; ميسم خدام (Latakia University Journal -Medical Sciences Series, 2024)
Aim of the study: This study aims to compare many methods of removing sealer residuals from pulp chamber to find the best way among them that make microleakage as little as possible. Materials and Methods: A sample of freshly extracted molars (n=120) was divided into 6 groups depending on the way sealer residuals were removed (n=20). Group 1: sealer residuals were removed by round TC burr. Group 2: were removed by a cotton pellet soaked in ethanol. Group 3: by air jet (glycine powder). Group 4: by air jet (sodium bicarbonate powder). Group 5: (control sample) by water/air spray. Group 6: (control sample) No sealer was applied. Then bond was applied and a Bulk composite after that and both were cured subsequently, finally, we used a dye penetration test to evaluate the microleakage of each group. Results: No statistically significant differences have been shown between the use of air polishing using glycine powder and the second control sample, while statistically significant differences appeared at a 95% confidence level between the rest of the sealant removal methods including the first control sample compared to the main (second) control sample. Conclusions: The use of air polishing to remove sealant residue had an important effect in eliminating marginal microleakage. The rest of the methods used did not eliminate marginal microleakage, and the use of air and water spray is considered the worst in terms of reducing marginal microleakage.